2003
DOI: 10.1172/jci16993
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disruption of γ-melanocyte–stimulating hormone signaling leads to salt-sensitive hypertension in the mouse

Abstract: IntroductionNumerous neural and humoral systems interact to control total body sodium content, body fluid volumes, and blood pressure through the regulation of urinary sodium excretion (U Na V). These include antinatriuretic pathways such as the renin-angiotensin system, aldosterone and sympathetic nerve activity to the kidneys, and natriuretic pathways such as the natriuretic peptide system (1, 2). Recent evidence has indicated that other natriuretic systems are involved in regulating U Na V, including dopami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
37
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 46 publications
5
37
0
Order By: Relevance
“…In general, salt and water homeostasis of the body is controlled by a bunch of neurohumoral factors. Some of these factors, such as vasopressin, oxytocin, melanocyte-stimulating hormone, uroguanylin, and the cardiac natriuretic peptides ANP and B-type natriuretic peptide (BNP), circulate in the plasma and are regulated by the salt intake [4,6,63,79,82,87] and, therefore, might be involved in the salt-dependent regulation of the renin system. In fact, the ANP appears to be the most ls ls + ACEI ctrl g g g Fig.…”
Section: Regulation Of Renin Synthesis and Release-general Aspectsmentioning
confidence: 99%
“…In general, salt and water homeostasis of the body is controlled by a bunch of neurohumoral factors. Some of these factors, such as vasopressin, oxytocin, melanocyte-stimulating hormone, uroguanylin, and the cardiac natriuretic peptides ANP and B-type natriuretic peptide (BNP), circulate in the plasma and are regulated by the salt intake [4,6,63,79,82,87] and, therefore, might be involved in the salt-dependent regulation of the renin system. In fact, the ANP appears to be the most ls ls + ACEI ctrl g g g Fig.…”
Section: Regulation Of Renin Synthesis and Release-general Aspectsmentioning
confidence: 99%
“…MC1R agonism causes darkening of skin and hair (Robbins et al, 1993) and reduces inflammation (Leoni et al, 2010; Li and Taylor, 2008) while loss of MC1R function reduces sensitivity to certain painful stimuli (Mogil et al, 2005; Mogil et al, 2003). MC3R contributes to the control of energy homeostasis (e.g., null mice are mildly obese (Butler et al, 2000; Chen et al, 2000a)), natriuresis (Ni et al, 2003), and inflammation, acting at least partially on macrophages (Getting et al, 2008). Genetic variation in MC3R may contribute to human obesity (Feng et al, 2005; Renquist et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…PC2-null mice also exhibit vulnerability, or lack of response to certain stresses. Ni et al (2003) have reported that after mild salt loading, PC2-null mice develop hypertension, which is not seen in wild-type mice, because of the lack of γ -MSH. Croissandeau et al (2006), on the contrary, have observed enhanced analgesia toward mechanical or thermal nociceptive stimuli in PC2-null mice.…”
Section: Introductionmentioning
confidence: 99%